Analysis of Road Network Performance in Pontianak at Jalan Sepakat 2 Reformasi, Padat Karya Using PTV VISUM - Pandia, Meri; Mayuni, Siti; Sumiyattinah, Sumiyattinah (Jurnal Teknik Sipil, 2024)
Jalan Sepakat 2, Reformasi, and Padat Karya are routes connecting strategic locations and educational institutions in Pontianak. As the population and economic activities grow, traffic volume increases, so a road performance analysis is needed to ensure the infrastructure can accommodate transportation needs and reduce potential congestion. This research uses primary data, such as road geometric data, traffic volume, and vehicle speed. Secondary data included location maps, population, motor vehicle numbers, trip generation, and attraction data. The analysis was based on the Indonesian Road Capacity Guidelines (PKJI) 2023 and PTV VISUM software. The analysis results 2024 showed a V/C Ratio of 0.59 with a service level of C and a speed of 31.18 km/hour. The 2029 projection shows a decline in performance with a V/C Ratio of 0.74, a service level of E, and a speed of 27.54 km/h. Jalan Reformasi was widened from 7.85 meters to 11 meters to improve performance, and Jalan Padat Karya from 6.25 meters to 8 meters. After the capacity increase, the 2029 projection shows improved performance, with the V/C Ratio decreasing to 0.63, the service level increasing to C, and the speed increasing to 31.27 km/h.